Di Garis Depan Perlindungan Anak: Strategi PTPAS Surakarta Melawan Kekerasan Seksual - Muzdalifah, Rina Arfiana; Wulandari, Murfiah Dewi (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2024)
Background: Sexual violence against children is a serious social issue that causes long-term psychological and emotional harm. In Surakarta, efforts to prevent such violence are implemented through the Integrated Service for Women and Children (PTPAS). Objective: This study aims to analyze the role of PTPAS Surakarta in preventing sexual violence against elementary school-aged children. Method: A qualitative case study approach was employed. Data were collected through in-depth interviews and document analysis, and analyzed using the interactive model by Miles and Huberman. Result: The most frequently reported types of violence were molestation and rape, with most perpetrators being from the victim's immediate environment. Key contributing factors included psychological disorders and lack of moral awareness. PTPAS played a preventive role through community education, psychosocial support, and facilitation of legal processes. Challenges faced included limited parental understanding and ineffective communication with children regarding sexual violence. Conclusion: The study highlights the importance of collaboration between institutions, schools, and families in building a comprehensive child protection system.